genius of place and time - Grigoryeva, Elena (project baikal, 2023)
The Latin expression genius loci has been most often applied to landscape, and we pay tribute to it already on the cover. But the same expression applies to a person who jealously preserves the unique atmosphere of a place. We state that a human being can spiritualise a place, i.e. become its genius. In 1817, five of Pushkin’s lyceum mates put a stone in the Tsarskoye Selo park with the inscription “To G.L. – genius of place”. More than two hundred years later, it seems appropriate for us, who recognise the City as a living organism with a soul, to talk about the genius of place. At the same time, realising the subtle connections between architecture and landscape, we include another dimension in the discussion – time. So what about time? The best minds of mankind have been reflecting on the essence of the relationship between Space and Time for millennia and continue to reflect on it today. For many centuries, Space and Time were the fundamentals that competed and even conflicted with each other. The procreative, feminine essence of Gaia (the Earth) opposed the destructive, transformative masculine essence of Chronos (the Time). Today, however, the pathos of struggle gives way to the search for unity. Following the new physics, which united space and time into a common continuum, we propose to search for variants of mutual complementation of these primary essences. Uniting geography with chronography (history) and geology with chronology (as well as geometry with chronometry) will not be easy. Both theorists and practitioners, as well as architectural historians, reflect on the problem. In this issue of our journal we have collected examples of the search for balance between time and place, between specific features of epochs and regions. As usual, this topic generates more questions than answers. But we are sure that we have found an appropriate time and place for such a discussion.
Keywords: genius loci; space; time; architecture